Analysis of Conservation-Based Tourism Potential at Pulo Tareba in Ternate City - Lely Adriani Nasution; Irfanto Umasangaji; Syarifuddin Adjam; Eva Marthinu; Vrita Tri Aryuni; Andi Tenri Pada Agustang (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2026)
Tourism development in small island areas requires an integrated approach that balances economic benefits with environmental protection to ensure ecological sustainability. Conservation-based tourism has become a strategic framework to minimize environmental degradation while supporting local livelihoods. Pulo Tareba, located in Ternate City, possesses significant ecological attributes, including a lake ecosystem, unique coastal landscapes, and biodiversity characterized by several endemic fauna species. However, pressure from poorly managed tourism activities that have not followed conservation principles has led to a decline in the population of endemic fauna such as the maleo bird, white cockatoo, Ternate lory, and blue-eyed cuscus. These four species play a vital role in the island's ecosystem balance. This study aims to analyze the potential of Pulo Tareba as a conservation-based tourism destination, with a focus on mitigation efforts to address the decline of endemic fauna populations. A qualitative case study approach was employed, with data collected through field observations, in-depth interviews, and documentation. The findings reveal that establishing protected status for Pulo Tareba and strengthening community participation in tourism management are essential to curb the rate of endemic species population decline and to achieve sustainable conservation-based tourism development in Pulo Tareba.